Sistem Informasi Manajemen Bank Sampah Dengan Notifikasi Instant Messaging Bot Telegram Menggunakan Metode RAD - Durbin Hutagalung, Deanna; Hanifurohman, Cholis; Rahadian Baskhara, Debby (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Waste banks are one solution in waste management using the 3R method (Reduce, Reuse, Recycle). However, in practice, many waste banks face obstacles in terms of information systems and services to customers, such as the delivery of balance information, transaction history, waste prices, and weighing schedules that are still manual. This is also experienced by the Kembang Sepatu Waste Bank located in Cirendeu Village, South Tangerang. To overcome this problem, researchers developed a Waste Bank Management Information System with Instant Messaging Notifications using the Rapid Application Development (RAD) Method. This study aims to design and implement an information system that can provide instant notifications to customers through a Telegram Bot. The system was designed with a RAD method approach consisting of three main phases: Requirement Planning, Design Phase, and Implementation Phase. The technologies used include Python as the backend, MySQL as the database, and the Telegram API for instant communication features. The implementation results show that the system can provide balanced information and transaction history automatically, provide real-time weighing notifications, and convey the latest waste price information through the Telegram bot. Furthermore, the system can forward specific questions from residents to the management team, maintaining responsive two-way interaction. This system improves the efficiency and transparency of waste bank services, which is expected to increase public participation in sustainable waste management.